2016
DOI: 10.1002/glia.23045
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and transcriptomics of peripheral nerve tissue and cells unravel new aspects of the human Schwann cell repair phenotype

Abstract: The remarkable feature of Schwann cells (SCs) to transform into a repair phenotype turned the spotlight on this powerful cell type. SCs provide the regenerative environment for axonal re-growth after peripheral nerve injury (PNI) and play a vital role in differentiation of neuroblastic tumors into a benign subtype of neuroblastoma, a tumor originating from neural crestderived neuroblasts. Hence, understanding their mode-of-action is of utmost interest for new approaches in regenerative medicine, but also for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
132
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 82 publications
(99 reference statements)
19
132
1
Order By: Relevance
“…22 Weiss et al 20 elegantly demonstrated that among the key factors associated with the repair programme, c-Jun was strongly expressed in human SC cultures and explants from peripheral nerve fascicles. 20 In the present study, we sought to determine the expression of this same transcription factor in the murine model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Weiss et al 20 elegantly demonstrated that among the key factors associated with the repair programme, c-Jun was strongly expressed in human SC cultures and explants from peripheral nerve fascicles. 20 In the present study, we sought to determine the expression of this same transcription factor in the murine model.…”
Section: Discussionmentioning
confidence: 99%
“…Büngner cells actively participate in the immune response, in addition to degrading myelin debris that could potentially inhibit axonal regeneration . The proto‐oncogene c‐Jun controls the conversion of Büngner cells after neural injury by mechanisms not yet fully clarified . C‐Jun is present at high levels in SCs prior to the establishment of the myelinating profile, and its expression is suppressed by Krox‐20 during cell maturation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human peripheral nerves were collected during reconstructive surgery, amputations or organ donations of male and female patients between 16 and 70 years of age. The ex vivo nerve injury model as well as the isolation procedure and culture conditions of primary human SCs have been performed as previously described Weiss et al, 2016 For IF analysis, SCs from 3 independent donors were co-cultured with STA-NB-6 or CLB-Ma NB cell lines in coated wells of an 8-well chamber slide (Ibidi), respectively, alongside with controls for 11 days.…”
Section: Human Peripheral Nerve Explants and Primary Schwann Cell Culmentioning
confidence: 99%
“…This phenotypical switch involves dedifferentiation into a proliferative state with immature/precursor SC properties and redifferentiation along an alternative pathway (Jessen & Mirsky, 2016). The resulting repair SC phenotype represents a transient cell state equipped with a certain skill set specialized to the needs during wound healing such as degradation of myelin debris, attraction of phagocytes, and the expression of cell surface proteins and trophic (neuroprotective and neuritogentic) factors promoting axon re-growth and pathfinding (Gomez-Sanchez et al, 2015;Jang et al, 2016;Jessen & Mirsky, 2016;Tofaris et al, 2002;Weiss et al, 2016). Furthermore, we have previously shown that human repair SCs express molecules involved in antigen processing and presentation via MHC-II as well as co-inhibitory receptors that support an immunomodulatory role of SCs during nerve regeneration .…”
Section: Introductionmentioning
confidence: 99%